2007
DOI: 10.1017/s0029665107005617
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic cross talk between the colon and the periphery: implications for insulin sensitivity

Abstract: Until recently, a glance at a standard undergraduate textbook would have given the impression that the colon was merely a storage organ for faeces and maybe something about the absorption of electrolytes and water. In reality, the colon is a highly-metabolically-active organ, the function of which has implications not only for the remainder of the digestive tract, but also for peripheral organs such as adipose tissue (AT), liver and skeletal muscle. The present review focuses on two distinct but complementary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 65 publications
(92 reference statements)
1
56
0
Order By: Relevance
“…Fructans consist of 1 glucose unit linked to a varying number of fructose units (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) present predominantly in the endosperm and germ tissues (19). Both branched and unbranched chains occur.…”
Section: Complex Carbohydrates In Whole-grain Cereals and Refined Promentioning
confidence: 99%
See 1 more Smart Citation
“…Fructans consist of 1 glucose unit linked to a varying number of fructose units (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) present predominantly in the endosperm and germ tissues (19). Both branched and unbranched chains occur.…”
Section: Complex Carbohydrates In Whole-grain Cereals and Refined Promentioning
confidence: 99%
“…Most SCFAs are absorbed by the colonic epithelium or metabolized by other colonic bacteria, resulting in only 5-10% of SCFAs being excreted in feces (8). SCFAs play an important role in gut and potentially metabolic health (9,12). The main purpose of the present review is to discuss current knowledge concerning the microbial degradation of complex carbohydrates from cereals and influence on SCFA production and impact on health.…”
Section: Introductionmentioning
confidence: 99%
“…The molar percentage enrichment of [6,6-2 H 2 ]glucose and the 13 C atom% were calculated as previously described (17) and smoothed by using the Optimized Optimal Segments (OOPSEG) program developed by Bradley et al (20). The rate of appearance (Ra) of total glucose in plasma (RaT) from exogenous (meal) and endogenous (hepatic) sources was calculated by using the nonsteady state equation of Steele et al (21) as modified by De Bodo et al (22).…”
Section: Glucose Kineticsmentioning
confidence: 99%
“…Several hypotheses as to how SCFAs mediate the glucose-lowering effect have been postulated. SCFAs may delay gastric emptying (12), have insulin-like properties (8), increase insulin sensitivity by decreasing free fatty acid (FFA) concentrations (13), have antiinflammatory effects (14), or promote insulin-independent glucose sparing.…”
Section: Introductionmentioning
confidence: 99%
“…Although a substantial part of the SCFA formed is extracted during passage of the liver (19), a fraction may enter the systemic circulation and can be determined in the peripheral blood (20). It has been suggested that certain SCFA may be involved in the modulation of glucose metabolism (14,16,21) and lipid metabolism (22) and it can be hypothesized that this may in fact be one possible mechanism whereby whole grain foods exert beneficial metabolic effects as seen in observational studies. However, whole grain foods are, in addition to being rich in DF, also rich in other potentially bioactive phytochemicals such as minerals, plant stanols and sterols, phenolic antioxidants, and vitamins (10,23).…”
Section: Introductionmentioning
confidence: 99%